Multipurpose Moxibustion Combined with Comprehensive Rehabilitation Training on Postoperation of Difficult Meningioma: A Case Report - Xiaoyan HUANG; Guifang WAN; Zulin DOU; Changcheng XU; Meng DAI; Luyu ZHAO; Xin LI; Jin ZHANG (康复学报)
Objective:To investigate the effect of multipurpose moxibustion combined with comprehensive rehabilitation training for a postoperative difficult meningioma patient.Methods:After applying traditional Chinese medicine (TCM) diagnostic protocol of looking, listening, asking and feeling the pulse in TCM to analyze the tumor patient's TCM syndrome types, we used different moxibustion in stages for treatment such as umbilical moxibustion, thunder-fire moxibustion, little grain moxibustion combined with comprehensive rehabilitation training such as speech and swallow training, cardiopulmonary rehabilitation training, physical therapy, occupation therapy.Results:After 10 months of treatment, the patient was successfully removed four tubes (urine tube, gas cut sleeve, nasal tube, and deep venous catheter).Conclusion:The multipurpose moxibustion combined with comprehensive rehabilitation training has remarkable curative effect on postoperation of difficult meningioma, but it is necessary to carry out case accumulation and systematic evaluation of efficacy.